Production of Open Cell Aluminium Metal Foam with Lost Foam Technique - Guler, Kerem Altug; Taslicukur, Zeynep; Ozer, Gokhan (CARL HANSER VERLAG, 2011)
Metallic foams represent materials with low densities as well as good physical, mechanical, thermal, and electrical properties. Since they have pores, metal foams have a set of unusual properties compared with bulk structural materials, i. e. the can offer a unique combination of several properties that can not be obtained in one conventional material at the same time. Metal foams can be produced by different processing technologies and many of them are still under development. The lost foam technique is an alternative foundry process as compared to other conventional techniques. This paper reports about a new approach for the production of open-cell aluminium foam metal by such casting procedure. During the process, an expanded polystyrene cell has been used for pattern making and all critical steps for manufacturing open-cell metal foam by the new technique are described in detail.
Keywords: Materials Science